Selenium intake and risk of type 2 diabetes among adults in Saudi Arabia - Alfawaz, Waad; Alharithy, Maha; AL-Musharaf, Sara; Aldhwayan, Madawi; Aljuraiban, Ghadeer S. (Frontiers in Endocrinology, 2025)
IntroductionRecent studies have demonstrated mixed findings regarding the intake of selenium (Se), an essential trace element for antioxidant defense and insulin metabolism regulation. Some studies have linked high Se intake to a higher risk of type 2 diabetes (T2DM), while others found protective or null associations. Se plays a dual role in that it aids pancreatic b-cell function and reduces oxidative stress, while excessive amounts disrupt redox balance and impair glucose metabolism.MethodsThe present study aimed to investigate the relationship between Se intake and markers of glucose metabolism in a cross-sectional sample of 1074 adults in Saudi Arabia with (n=213) and without (n=861) T2DM as determined by physician diagnosis. Dietary Se intake was assessed using a validated Saudi Food Frequency Questionnaire and analyzed with ESHA software. Sociodemographic, anthropometric, clinical, and lifestyle data were collected. The relationships between Se intake and the presence of a T2DM diagnosis, fasting blood glucose (FBG), fasting insulin, and Homeostatic Model Assessment of Insulin Resistance (HOMA-IR), were assessed using multivariate linear and logistic regression analyses, adjusting for age, sex, education, income, body mass index, physical activity, smoking, medication use, and family history of T2DM.ResultsThe average Se intake was lower in adults with T2DM compared to those without (20 mg/1000 kcal and 38 mg/1000 kcal, p<0.0001, respectively). Multivariate linear regression analysis demonstrated no statistically significant association between the Se intake and FBG, HOMA-IR index, and fasting insulin levels after adjustments. Multivariate logistic regression revealed a significant association between dietary Se and a diagnosis of T2DM when fully adjusted [OR 0.8 (95% CI: 0.7, 0.9, P<0.05)].DiscussionIn conclusion, our research found that Saudi adults with relatively higher Se intake had lower odds of T2DM diagnosis, while no significant relationships were found between Se intake and glycemic biomarkers. Future studies incorporating longitudinal data and serum Se levels can further clarify the relationship.